Food Creatine and Head Circumference Among Children Aged 0–2 Years. (14th June 2022) - Ostojic, Sergej; Korovljev, Darinka; Stajer, Valdemar; Todorovic, Nikola
Abstract: Objectives: Several small-scalle studies demonstrated an association between dietary creatine intake and body size in school-aged children and adolescents, yet no such connection has been evaluated in very young children at the populational level. We conducted a secondary analysis of previously completed cross-sectional study, and determined an association between food creatine and body measures in 597 U.S children aged 0 to 2 years, using the 2017–2018 National Health and Nutrition Examination Survey database. Methods: Total grams of creatine consumed per day were computed using the average amount of creatine ( e.g., 0.20 g/kg for milk-based foods and 3.88 g/kg for meat-based sources) across all creatine-containing food sources. Results: Dietary creatine intake was positively correlated with head circumference ( r  = 0.184; P  = 0.031) when controlled for age at screening, while no link was found between creatine consumption and recumbent length ( r = - 0.003; P  = 0.955) or body weight (r = 0.048; P  = 0.317). A multiple regression analysis revealed a significant relationship between food creatine and head circumference ( P < 0.001) when adjusted for the effects of selected dietary variables (e.g., weight of food consumed, total caloric content, protein intake). Conclusions: Our findings indicate a relationship between food creatine and head circumference as a surrogate marker of brain size in early childhood; further pediatric studies should appraise the role of dietary creatine in neurodevelopment. Funding Sources: N/A.